The COVID-19 pandemic has highlighted the need to invest in care home research infrastructure. (17th February 2022) - Gordon, Adam L; Rick, Caroline; Juszczak, Ed; Montgomery, Alan; Howard, Rob; Guthrie, Bruce; Lim, Wei Shen; Shenkin, Susan; Leighton, Paul; Bath, Philip M; ,
Abstract: The COVID-19 pandemic resulted in catastrophic levels of morbidity and mortality for care home residents. Despite this, research platforms for COVID-19 in care homes arrived late in the pandemic compared with other care settings. The Prophylactic Therapy in Care Homes Trial (PROTECT-CH) was established to provide a platform to deliver multi-centre cluster-randomized clinical trials of investigational medicinal products for COVID-19 prophylaxis in UK care homes. Commencing set-up in January 2021, this involved the design and development of novel infrastructure for contracting and recruitment, remote consent, staff training, research insurance, eligibility screening, prescribing, dispensing and adverse event reporting; such infrastructure being previously absent. By the time this infrastructure was in place, the widespread uptake of vaccination in care homes had changed the epidemiology of COVID-19 rendering the trial unfeasible. While some of the resources developed through PROTECT-CH will enable the future establishment of care home platform research, the near absence of care home trial infrastructure and nationally linked databases involving the care home sector will continue to significantly hamper progress. These issues are replicated in most other countries. Beyond COVID-19, there are many other research questions that require addressing to provide better care to people living in care homes. PROTECT-CH has exposed a clear need for research funders to invest in, and legislate for, an effective care home research infrastructure as part of national pandemic preparedness planning. Doing so would also invigorate care home research in the interim, leading to improved healthcare delivery specific to those living in this sector.